Acidification treatment of lignin from sugarcane bagasse results in fractions of reduced polydispersity and high free-radical scavenging capacity - Brenelli, Lívia Beatriz; Mandelli, Fernanda; Mercadante, Adriana Zerlotti; Rocha, George Jackson de Moraes; Rocco, Silvana Aparecida; Craievich, Aldo Felix; Gonçalves, Adilson Roberto; Centeno, Danilo da Cruz; de Oliveira Neto, Mario [UNESP]; Squina, Fabio Marcio (Elsevier, 2016)
Lignin constitutes up to one-third of the material found in plant cell walls and is considered the second most abundant natural polymer in the world. Despite unique characteristics of lignin, it is mostly used for low-value commercial applications. In this study, lignin obtained after alkaline treatment of steam-exploded sugarcane bagasse was submitted to an acidification process. The soluble fractions produced at different pH values were comprehensively characterized and in vitro antioxidant capacity against reactive oxygen (ROO and H2O2) and nitrogen (ONOO-) species was evaluated. The soluble fraction obtained at pH 2 exhibited the highest scavenging capacities against all species tested (10.2±0.7mmol Trolox equivalent g-1 for ROO, IC30=14.9μgmL-1 for H2O2 and IC50=2.3μgmL-1 for ONOO-) and the lowest polydispersity value (1.2) compared to others fractions. According to the SAXS data, the soluble fractions obtained at pH 4 and pH 2 consisted of small nanometer-sized discs and low molecular weight polyphenolic clusters, while soluble fractions obtained at high pH predominated wide lignin nanoparticles and larger aggregates. Mass spectroscopy analysis revealed the presence of phenolic and non-phenolic compounds, well-known as efficient antioxidants, which were identified in all soluble fractions. Collectively, our results provided further demonstration that acidification treatment is a promising strategy to upgrade heterogeneous lignin-enriched stream from sugarcane bagasse, such as preparations with homogeneous compositions and high antioxidant activity.
Keywords: Lignin; Reactive nitrogen species; Reactive oxygen species; Small-angle X-ray scattering; Sugarcane bagasse